Detection and identification of Fabavirus species by one-step RT-PCR and multiplex RT-PCR - Panno, Stefano; Ferriol, Inmaculada; Rangel, Ezequiel A.; Olmos, Antonio; Han, Cheng-Gui; Martinelli, Federico; Rubio, Luis; Davino, Salvatore (2017)
The genus Fabavirus of the family Secoviridae comprises a group of poorly characterized viruses. To date, only five species have been described: Broad bean wilt virus 1 (BBWV-1), Broad bean wilt virus 2 (BBWV-2), Lamium mild mosaic virus (LMMV), Gentian mosaic virus (GeMV) and Cucurbit mild mosaic virus (CuMMV). The development is described of two RT-PCR procedures for the detection and identification of Fabavirus species: a one-step RT-PCR using a single pair of conserved primers for the detection of all fabaviruses, and a one-step multiplex RT-PCR using species-specific primers for the simultaneous detection and identification of the above-mentioned species of the genus Fabavirus. These methods were applied successfully to field samples and the results were compared with those obtained by molecular hybridization and ELISA. The combination of the two techniques enables rapid, sensitive and reliable identification of the five known fabavirus species, as well as the possibility of discovering new species of this genus. (C) 2013 Elsevier B.V. All rights reserved.